ICE STORAGE CHARACTERISTICS OF PERCH WITH SPECIAL REFERENCE TO ITS SUITABILITY FOR CANNING. - SOLANKI, K K; RADHAKRISHNAN, A G; JOSEPH, JOSE; VENKATARAMAN, R (Fishery Technology, 2017)
Perch (Pagrus spinifer), one of the most abundantly available fishes of Gujarat coast, was subjected to a detailed study for assessing its storage life in ice and amenability of the iced fish for canning. Changes in the salt soluble nitrogenous material and myosin content of the iced fish showed good correlation with the changes in the organoleptic and physical qualities. The fish was found to have a storage life of 9 days in ice and samples stored upto 7 days were suitable for canmng.